An Alternative Technique for Prevention of Lateral Tibial Plateau Fractures During The Proximal Tibial Medial Opening Wedge Osteotomy: An Experimental Study At Calf Tibiae (Annals of Medical Research, 2021)
None
Keywords: Proximal tibial osteotomy, High tibial osteotomy, Complications, Experimental study, Lateral tibial plateau fractures, Technical trick